Tranexamic acid to reduce bleeding after dental extraction in patients treated with non-vitamin K oral anticoagulants: design and rationale of the EXTRACT-NOAC trial. Issue 10 (December 2019) - Ockerman, A.; Vanhaverbeke, M.; Miclotte, I.; Belmans, A.; Vanassche, T.; Politis, C.; Jacobs, R.; Verhamme, P.
Abstract: Bleeding after dental extraction in patients treated with non-vitamin K oral anticoagulants (NOAC) may lead to unplanned reinterventions and interruption of anticoagulation, thereby exposing patients to a risk of thromboembolism. We have designed a study (EXTRACT-NOAC) to investigate whether tranexamic acid (TXA) mouthwash decreases bleeding after extraction in such patients. The study is a randomised, double-blind, placebo-controlled trial. We plan to randomise 236 patients listed for dental extraction and treated with NOAC to 10% TXA mouthwash or placebo. Patients are instructed to use the mouthwash before the dental extraction, and three times a day for three days thereafter. The primary outcome is oral bleeding. Secondary outcomes include type of bleeding, procedural bleeding score, number of reinterventions after oral bleeding, and number of interruptions in NOAC treatment. Any bleeding from sources other than the mouth, and thrombotic events, are recorded as safety outcomes. Patients are followed-up for seven days. This study will provide evidence to guide the management of patients taking NOAC who need teeth extracted.